Pharmacokinetic-pharmacodynamic target attainment analyses as support for meropenem dosing regimens in critically ill adult and elderly patients with Pseudomonas aeruginosa infections - Tao, Ruyu; Chan, Sumyeut; Wang, Jinxingyi; Wang, Xianhe; Shi, Lei; Lan, Xue; Chen, Ling; Mu, Xiaohui (Frontiers in Pharmacology, 2025)
BackgroundCritically ill patients often undergo profound pathophysiological changes that alter the pharmacokinetics (PK) of hydrophilic antibiotics such as meropenem. These changes, combined with bacterial susceptibility, may reduce antimicrobial efficacy. This study aimed to optimize meropenem dosing regimens for adult and elderly critically ill patients with Pseudomonas aeruginosa infections using a model-informed approach.MethodsLimited PK sampling and therapeutic drug monitoring (TDM) data were analyzed to develop a population PK model. Covariates were evaluated, and Monte Carlo simulations (n = 1,000 virtual patients) were conducted to assess alternative dosing strategies, including 0.75–3 g/day (0.5 h infusion) and 0.5–1.5 g every 6–8 h. Probabilities of target attainment (PTA; 40% fT > MIC ×4 and 100% fT > MIC ×4) and cumulative fraction of response (CFR) were calculated.ResultsA one-compartment model with age-adjusted distribution volume best described the data. Population PK estimates were 4.68 L/h for clearance and 4.47 L for distribution volume, both with <50% variability. Age was a significant covariate, with Vd increasing progressively with advancing age. Simulations showed that 750 mg loading followed by 500 mg every 6 h achieved ≥90% CFR in 90-year-old patients, whereas 1 g loading plus 3 g/day (four times daily) was optimal for 40–60-year-old adults.ConclusionsAge-related increases in meropenem distribution volume necessitate tailored dosing regimens in critically ill patients. More frequent administration (q6h) improved CFR, particularly in elderly populations. Model-informed precision dosing may enhance treatment success against P. aeruginosa infections in intensive care settings.